2021
DOI: 10.1016/j.jenvman.2021.112852
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ibuprofen on extracellular polymeric substances (EPS) production and composition, and assessment of microbial structure by quantitative image analysis

Abstract: A Sequencing Batch Reactor (SBR) with activated sludge was operated with synthetic wastewater containing ibuprofen (IBU) to investigate the biomass stress-responses under long-term IBU exposure. There were 3 different phases: phase I as the control without IBU for 56 days, phase II (40 days), and phase III (60 days) containing IBU at 10 and 5 mg L − 1 each. The overall performance of the SBR as well as the extracellular polymeric substances (EPS) in terms of polysaccharides, proteins, and humic acid substances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
3
11
0
Order By: Relevance
“…In this work, a sequencing batch reactor (SBR) with a working volume of 2 L was inoculated with AS from a full-scale WWTP and fed with synthetic wastewater (the composition can be found in [23]). The initial mixed liquor suspended solids (MLSS) in the system was ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, a sequencing batch reactor (SBR) with a working volume of 2 L was inoculated with AS from a full-scale WWTP and fed with synthetic wastewater (the composition can be found in [23]). The initial mixed liquor suspended solids (MLSS) in the system was ca.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of chemical oxygen demand (COD), ammonium (NH 4 + -N), nitrite (NO 2 − -N), and nitrate (NO 3 − -N) was performed as described by Melo et al [23]. MLSS, mixed liquor volatile suspended solids (MLVSS), and the sludge volume index at 30 min (SVI) were determined in accordance with standard methods [24].…”
Section: Methodsmentioning
confidence: 99%
“…Large amounts of DNA in the EPS may indicate that the cells suffered cell lysis during the rigorous extraction process (Liu and Fang, 2002). Besides, amphiphilic compounds (phospholipids), glycosylated proteins (glycoproteins), and HAS have also been shown to appear in significant amounts or even predominate in EPS preparations from AS, trickling filter biofilms, and anammox granular sludge (Boleij et al, 2018;Oliveira et al, 2020;Liu et al, 2021;Melo et al, 2021). Additionally, HAS are constituted of complex heterogeneous mixtures of organic compounds, such as polyaliphatic and poly-aromatic compounds, containing carboxylic, phenolic, and hydroxyl, which give a highly negative charge.…”
Section: Definition and Compositionmentioning
confidence: 99%
“…For instance, Shen et al (2020) found that EPSt production decreased with a bulking phenomenon. Furthermore, the research work of Melo et al (2021) revealed that, despite the poor floc structure, the rising in EPS content, especially TB-EPS, was the critical point to reaching an AS with wellsettling ability properties. In turn, PN and DNA content in EPS seems to have more significant effects on the settling ability of microbial aggregates, presenting a positive relationship with SVI, and it was not possible to establish a relationship between PS and SVI (Sheng et al, 2010).…”
Section: Settling Abilitymentioning
confidence: 99%
See 1 more Smart Citation